Fermentation of Dioscorea hispida Oligosaccharides by Lactic Acid Bacteria and Bifidobacterium - Napisah, Hussin; Rosma, Ahmad (2020)
Dioscorea hispida oligosaccharides (DHOS) were intended to be used as a synbiotic product. Fermentability of DHOS by lactic acid bacteria and Bifidobacterium was studied. In vitro DHOS fermentations by L. acidophilus FTDC 2131, L. casei ATCC 393, L. casei FTCC 0442, L. plantarum FTCC 0350 and B. bifidum 12 were at 37°C for 24 h. DHOS was the most preferred substrate by L. acidophilus FTDC 2131, L. plantarum FTCC 0350 and B. bifidum 12, whilst, fructooligosaccharides (FOS) and inulin was the best substrate for the growth of L. casei ATCC 393 and L. casei FTCC 0442, respectively. The pH reduction in DHOS fermentation medium was comparable to the commercial FOS suggesting that DHOS was able to enhance the selected bacterial growth and produced organic acids. Fermentation of DHOS by B. bifidum 12 had exhibited the highest prebiotic activity score (+0.713) and produced 30.42 mM lactic , 22.63 mM acetic and 0.71 mM propionic acids. The incorporation of DHOS in the medium culture of the selected bacteria was able to enhance the bacterial growth, reduce the pH medium, produce substantial amount of lactic , acetic and propionic acids, and exhibit positive prebiotic activity score.